Simultaneous Determination of Speed of Sound and Sample Thickness Utilizing Coded Excitation - Rupitsch, Stefan; Glaser, Daniel; Lerch, Reinhard (IEEE SERVICE CENTER, 445 HOES LANE, PO BOX 1331, PISCATAWAY, NJ 08855-1331 USA, 2012)
We propose an approach to simultaneously identify the speed of sound (SOS) in a flat homogeneous material specimen and its thickness by means of ultrasound. Basically, the setup operating in transmission mode consists of an ultrasound transducer and an opposed hydrophone. In contrast to common approaches, where short broadband pulses are utilized, the ultrasound transducer is here excited with a continuous sinusoidal signal being phase-modulated. The phase modulation is carried out with a Gold sequence offering outstanding correlation properties. In order to determine SOS and sample thickness, the time-of-flight (TOF) for sound waves propagating directly from transducer to hydrophone as well as for those being multiple reflected within the specimen is analyzed. For this purpose, we perform two subsequent signal processing steps: (i) signal correlation, and (ii) numerical search for multiple reflections. As the results for different solid material specimen reveal, the approach yields precise values for both, SOS and sample thickness.